التحکیم الالکترونی فی المنازعات الخاصة الدولیة - سلطان عبدالله الجواری (University of Mosul-college of Basic Education, 2021)
Electronic arbitration is considered one of the important means of dispute settlement due to its speed, flexibility and ease that may not be present in the ordinary judiciary either, not even in ordinary arbitration, whether internal or external. Ordinary arbitration, in addition to lengthy procedures and high costs, does not Fits the speed needed by trade in our time, and through this research we will try to shed light on the disputes of electronic arbitration and try to find solutions to this problem.Electronic arbitration is considered one of the important means of dispute settlement due to its speed, flexibility and ease that may not be present in the ordinary judiciary either, not even in ordinary arbitration, whether internal or external. Ordinary arbitration, in addition to lengthy procedures and high costs, does not Fits the speed needed by trade in our time, and through this research we will try to shed light on the disputes of electronic arbitration and try to find solutions to this problem.